Silver nanoparticles effects on dendritic cells: toxicity and phenotypic implications; European Journal of Immunology (EJI); Vol. 48, iss. S1 : 15th International Symposium on Dendritic Cells - Garcia-Garcia M. R. Maritza; Castro-Gamboa S.; Pinon-Zarate G.; Rojas-Lemus M.; Jarquin-Yanez K.; Herrera-Enriquez M. A.; Fortoul van der Goes T. I.; Garcia-Iglesias T.; Pestryakov A. N. Aleksey Nikolaevich (2018, 2018)
Title screen